Athletes United for Peace: Reconciliation through Sport - Irene Kamberidou (Proceedings of the international conference SPORT AS A MEDIATOR BETWEEN CULTURES, 2012)
Policy makers consider that sport contributes to a wide range of ideals such as intercultural understanding, reconciliation, social integration. Grassroots programmes involving tens of thousands participants around the globe from visionaries, educators, civic acitivists, volunteers, etc. are using sport to tackle the most pressing problems of the developing world—from AIDS in Africa to violence in Rio and Haiti. Is this the vision of salvation through sport too grandiose? Can such projects make a lasting difference? Remarkable results have been documented by many NGOs that have been using sport as a tool to promote reconciliation and respect for ethnic diversity. Sport is considered a vital space, especially  in light of today’s xenophobic worldviews. (See proceedings) ------------------------------------------------------------------------------------------------------------ Kamberidou, I. (2012). Athletes United for Peace: Reconciliation through Sport. Proceedings of the international conference SPORT AS A MEDIATOR BETWEEN CULTURES, pp. 187–202. International Council of Sport Science and Physical Education (ICSSPE/CIEPSS), Hanns-Braun-Strase Friesenhaus II D-14053 Berlin. Editors Ronnie Lidor, Karl-Heinz Schneider & Katrin Koenen. ISBN 978-3-9811179-4-3 , copyright 2012 by ICSSPE. D.4 in Apella